Socio-economical Characteristics and Determinants of Indonesian National Health Insurance Subsidized By The Government in Jakarta - dr. Jeffrey Christian Mahardhika (Medical Clinical Update, 2023)
The National Health Insurance Program (Jaminan Kesehatan Nasional - JKN) is a social health insurance managed by the National Health Insurance Agency (Badan Penyelenggara Jaminan Sosial Kesehatan – BPJS Kesehatan), aiming to provide health insurance for all Indonesian people. Community groups that receive subsidies from the government are referred to as Contribution Assistance Recipients (Penerima Bantuan Iuran - PBI) participants. One of the issues regarding the JKN program so far is the inaccuracy of PBI targets. Therefore, a study is needed to evaluate the relationship between JKN PBI ownership with their socioeconomic status and history of receiving social aid.